Basement maintenance / Suhana Zainal Abidin - Zainal Abidin, Suhana (2002)
The title of this dissertation is 'BASEMENT MAINTENANCE'. It is involves all about the maintenance and the basement. Basement is the lowest storey in a structure where designed to provide working area below ground level and act as the foundation for the building itself. While maintenance is the works or combination of activity or action that is undertaken in order to keep, restore and retain of every facilities such as its services and surrounds to an agreed and acceptable standard to sustain the utility and value of the facility to a state which the building cart perform its required function. The main function of basements is to provide additional space in the sub-structure of the building and in some cases, basement may be required for their function in reducing net bearing pressure. The normally uses of basements is underground car parking. The underground car parking will also can reduce the area of the off-site or expose car parking. For basement construction, it is important to concern about the waterproofing system. The main requirement of basement is watertightness. It is important to give a very high commitment during design stage and construction of the waterproofing system. Buildings will endure their expected lifetime if adequately maintained, which is the main principle of preventive maintenance. Preventive Maintenance is most effective when it deals with potential failures and prevents actual failures. Preventive maintenance consists of taking preventive action in order to avoid expected failures and the maintenance is carried out through periodic inspection and replacement of the critical part. The quality of waterproofing system should be weighed against anticipated Preventive Maintenance requirements. This process should be employed during the initial stages of the project development that is during the design stage. Design, construction detailing and installation play a critical role in the maintenance of the building system. Maintenance of poorly constructed systems is generally wasteful and extremely costly.